(untitled) (International Journal of Innovative Computing, 2021)
Increase in the adoption of ICT for service provision renders higher educational institutions in Nigeria vulnerable to numerous security challenges. The information security threats addressed in this paper encompasses identity theft and identification frauds. The high number of students patronizing these institutions seeking for knowledge results in the challenges of identifying authentic students. The use of students’ identification number and password is no longer sufficient for authentication of students. Therefore, this paper proposed a centralized authentication model for higher education system (CAMHES) for Nigeria. The model uses multi-factor authentication combining students’ identification number, students’ fingerprint biometric and smartcard technology for students’ authentication. The solution authenticates the identity of genuine students to eliminate impersonation in Nigerian higher education systems. Although, this solution provides authentication that is extremely difficult to replicate, it is recommended that the students’ biometric data captured must be strictly kept safe.